Gambus Academy Kindang: Revitalisasi Musik Tradisi Bugis-Makassar Berbasis Inovasi Digital untuk Literasi Budaya Generasi Muda Bulukumba - Buchary Pasyah, Soekarno; Kadir, Irsan; wahid, abd; Zia Ulhaq, Muhammad (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
The Gambus Academy Kindang program was implemented as an effort to revitalize Bugis–Makassar traditional music through artistic training, cultural literacy enhancement, and the integration of digital technology among youth in Kindang Village, Bulukumba Regency. This initiative responds to the fact that most young people are no longer familiar with the basic techniques of Gambus playing, traditional repertoires, or the cultural meanings embedded within this musical heritage. The program adopted a community-based participatory approach by involving a local Gambus maestro, facilitators, and participants as active agents throughout the learning process. The training activities included the introduction of Gambus history and philosophy, basic plucking techniques, fingering, mastery of traditional repertoires, audio-video recording, content editing, and the development of cultural education materials.The results indicate a significant improvement in both technical competence and cultural understanding. The average score for basic Gambus-playing skills increased from 25.7 in the pre-test to 75 in the post-test, while participants’ cultural attitudes and literacy improved from 2.27 to 4.37 on a 1–5 scale. Youth who initially perceived Gambus as outdated music began to show pride in Bugis–Makassar cultural identity and recognized the social and ritual functions of Gambus within traditional ceremonies. Moreover, the acquisition of digital skills enabled participants to produce cultural content accessible to broader audiences. The program also enhanced participants’ motivation and self-confidence, evidenced by their initiative to practice independently and their readiness to perform in public showcases. Overall, Gambus Academy Kindang has proven effective as a model for preserving traditional arts by integrating local wisdom with digital innovation.